2017
DOI: 10.18632/oncotarget.16565
|View full text |Cite
|
Sign up to set email alerts
|

Preferential accumulation of regulatory T cells with highly immunosuppressive characteristics in breast tumor microenvironment

Abstract: Immunosuppressive cells such as regulatory T cells (Tregs) have an ambiguous role in breast cancer prognosis, with studies reporting both positive and negative correlations between Treg infiltration and prognosis. This discrepancy could be due to the different immunosuppressive molecules present in these cells. In the present study, we phenotypically characterize different Treg subsets infiltrating the tumor microenvironment (TME), compared to adjacent normal tissue and peripheral blood of primary breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…These data are supported by several studies, including an analysis of >100 treatment naïve BC patients where Treg abundance in the tumor microenvironment was characterized by high levels of surface CCR8, CTLA-4, and PD-1 ( 69 ). Another study similarly found that FOXP3 + Helios + CTLA-4 hi PD-1 hi CD4 + TIL characterize Tregs infiltrating BC ( 28 ). Overall, current findings indicate that dual checkpoint inhibition targeting CTLA-4 and PD-1 potentially has important synergistic effects due to their distinct regulatory activities ( 70 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These data are supported by several studies, including an analysis of >100 treatment naïve BC patients where Treg abundance in the tumor microenvironment was characterized by high levels of surface CCR8, CTLA-4, and PD-1 ( 69 ). Another study similarly found that FOXP3 + Helios + CTLA-4 hi PD-1 hi CD4 + TIL characterize Tregs infiltrating BC ( 28 ). Overall, current findings indicate that dual checkpoint inhibition targeting CTLA-4 and PD-1 potentially has important synergistic effects due to their distinct regulatory activities ( 70 ).…”
Section: Discussionmentioning
confidence: 93%
“…No clinical significance has been attributed to expression of the alternate PD-1 ligand PD-L2 ( 27 ). The first immune checkpoint molecule targeted in the clinic, CTLA-4, was analyzed in BC with the presence of CTLA-4 + , PD-1 + , Helios + , FOXP3 + , GITR + , and/or CD103 + Tregs suggestive of an immunosuppressive microenvironment ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the expression of multiple immune checkpoints in the peripheral blood of primary breast and colorectal cancer patients compared with healthy donors. Studies reported that expressions of multiple ICs including PD-1 and CTLA-4 were elevated in the circulation of both PBC 19,20 and CRC. 21 We have recently reported that the promoter demethylation and post-translational histone modifications play a role in the regulation of immune checkpoints in PBC and CRC tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The triple-negative BC (TNBC) subtype is the most aggressive subtype, and it is further classified into four subtypes: luminal/androgen receptor (LAR), mesenchymal (MES), basal-like immune suppressed (BLIS), and basal-like immune activated (BLIA) subtypes (4). The triplenegative subtype was demonstrated in several studies to frequently express the programmed cell death-ligand 1 (PD-L1) (5,6); there exist an overall immune system dysfunction and suppression throughout different BC subtypes due to the abundance of immune suppressive cells, namely, regulatory T cells (Tregs), and myeloid-derived suppressor cells (MDSCs), within the BC tumor microenvironment (7).…”
Section: Introductionmentioning
confidence: 99%